Torsion-free groups with every proper homomorphic image an N₁-group - Ercan, S. (Algebra and Discrete Mathematics, 2004)
In this article it is proved that a torsion-free locally nilpotent groups with non-trivial Fitting subgroup and every proper homomorphic image an N₁-group is an N₁-group(and so it is nilpotent).